1997
DOI: 10.5271/sjweh.180
|View full text |Cite
|
Sign up to set email alerts
|

Subjective symptoms among motorcycling traffic policemen

Abstract: Objectives This study investigated the prevalence of subjective symptoms among current and forn~er motorcycling policemen. Methods The subjects of this study consisted of 46 current and 72 former inotorcycling traffic policemen from a certain city located in the central part of Japan. They were requested to reply to questions on a selfadministered questionnaire regarding age, work history, and subjective symptoms (16 items) during the month preceding the completion of the questionnaire. Results Shoulder stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Police and law enforcement officers may also suffer, because of their occupation, reactive airway dysfunction syndrome (RADS) (Promisloff, Phan, Lenchner, & Cichelli, 1990) and have increased risks of cancer from radar equipment (Davis & Mostofi, 1993;DeWitt, 1991). Police and law enforcement officers also suffer from increased risks of back and other musculoskeletal injuries (Mirbod, Inaba, & Iwata, 1997) due to long periods riding in automobiles and on motorcycles.…”
Section: Decrements In Health Performance With Advanced Ageingmentioning
confidence: 99%
“…Police and law enforcement officers may also suffer, because of their occupation, reactive airway dysfunction syndrome (RADS) (Promisloff, Phan, Lenchner, & Cichelli, 1990) and have increased risks of cancer from radar equipment (Davis & Mostofi, 1993;DeWitt, 1991). Police and law enforcement officers also suffer from increased risks of back and other musculoskeletal injuries (Mirbod, Inaba, & Iwata, 1997) due to long periods riding in automobiles and on motorcycles.…”
Section: Decrements In Health Performance With Advanced Ageingmentioning
confidence: 99%
“…But little is known about overuse injuries of off -road-motorcyclists. The incidence of overuse syndromes was observed in 19 police offi cers, who used routinely motorcycles [1] . Raynaud syndrome was recorded in 4.2 % , myogelosis in the cervical spine and pain in the shoulders in 5.0 -19.3 % .…”
Section: Introduction ▼mentioning
confidence: 99%
“…It was previously shown that driving a surveillance vehicle or motorcycle causes shoulder, arm and neck complaints as a result of total body vibrations (6,7,8). They are exposed to cold weather and may experience increased tension in hands and arms or physical stress due to awkward positioning of the upper body.…”
Section: Introductionmentioning
confidence: 99%